2010
DOI: 10.1515/cclm.2010.011
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the cardiac marker N-terminal-pro brain natriuretic peptide through adjustment for renal function: a stratified multicenter trial

Abstract: Background: N-terminal-pro brain natriuretic peptide (NTproBNP) is a useful cardiac marker that is also influenced by renal dysfunction. It was our objective to assess the relationship between NT-proBNP concentrations in plasma and worsening renal function, and to attempt adjustment of NTproBNP for renal dysfunction in a prospective, stratified multi-center study. Methods: We stratified 203 male patients according to their cardiac status and the estimated glomerular filtration rate (eGFR). Cardiac disease was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Laboratory parameters were determined using automated Siemens autoanalyzers (Advia 1800 and Immulite 2000). N-terminal pro brain natriuretic peptide (NT-pro-BNP) was corrected for Modification of Diet in Renal Disease GFR according to the formula by Luchner et al (23). Serum aldosterone and plasma renin activity were measured manually using RIA methods (Immunotech, Prague, Czech Republic and Zentech, Angleur, Belgium).…”
Section: Laboratory Assaysmentioning
confidence: 99%
“…Laboratory parameters were determined using automated Siemens autoanalyzers (Advia 1800 and Immulite 2000). N-terminal pro brain natriuretic peptide (NT-pro-BNP) was corrected for Modification of Diet in Renal Disease GFR according to the formula by Luchner et al (23). Serum aldosterone and plasma renin activity were measured manually using RIA methods (Immunotech, Prague, Czech Republic and Zentech, Angleur, Belgium).…”
Section: Laboratory Assaysmentioning
confidence: 99%
“…A study from our group has previously validated the usefulness of N‐terminal proB‐type natriuretic peptide (NT‐proBNP) measurements in the diagnosis of LVD associated with AECOPD, 10 where natriuretic peptides may be liberated by alternative mechanisms such as those associated with pulmonary hypertension, hypoxaemia and right ventricular stress, 11 and accounting for the higher threshold values compared with those in patients with isolated LVD 10,12 . Patients with severe renal impairment were, however, excluded, since natriuretic peptides are removed from the circulation by the kidneys and may be markedly elevated in terminal renal failure without associated LVD 13–18 . However, recent studies have suggested that natriuretic peptides may still show good discriminative power for the diagnosis of cardiac dysfunction even in patients with renal impairment 19–22 …”
Section: Introductionmentioning
confidence: 99%
“…10,12 Patients with severe renal impairment were, however, excluded, since natriuretic peptides are removed from the circulation by the kidneys and may be markedly elevated in terminal renal failure without associated LVD. [13][14][15][16][17][18] However, recent studies have suggested that natriuretic peptides may still show good discriminative power for the diagnosis of cardiac dysfunction even in patients with renal impairment. [19][20][21][22] The present study was conducted in order to evaluate the performance of NT-proBNP measurements in the diagnosis of LVD associated with AECOPD in patients with or without renal dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we also examined the associations between baseline NT-proBNP and changes in BP in the overweight segment of “the incident study population”, and although not statistically significant ( P = 0.13), one SD lower NT-proBNP concentration at baseline was associated with a 0.5 mm Hg higher SBP at follow-up taking use of antihypertensive medication into account [ 25 ]. Finally, excluding participants with serum concentrations of NT-proBNP exceeding 200 pg/mL (n = 156), indicative of subclinical structural heart disease [ 26 ], or applying the NT-proBNP adjustment algorithm, as suggested by Luchner et al [ 27 ], did not change the results in the main analyses (data not shown).…”
Section: Resultsmentioning
confidence: 99%